2020
DOI: 10.4028/www.scientific.net/kem.842.231
|View full text |Cite
|
Sign up to set email alerts
|

Acetone Sensing Properties of NiO Nanofibers Based on Electrospinning

Abstract: Acetone is a main respiratory marker for diabetic patients. In this paper, P-type NiO nanofibers were prepared by electrospinning and used for the detection of acetone gas. NiO nanofibers were characterized by SEM and XRD. The uniform NiO nanofibers with face-centered cubic structure was obtained. The working temperature of NiO nanofibers was optimized, and the optimal operating temperature is 220°C. The response-recovery curve was tested, and the response and recovery time is 24.6 s and 610 s respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, due to the unique electrochemical characteristics of NiO, composite materials based on it can be used in various gas sensitive systems. For example, Fan X. et al [15] note the possibility of using a p-type composite based on NiO as a sensor for detecting gaseous acetone. Experimental results showed that the applied composite had an optimum sensor op-erating temperature in the range of 220 °C and sensitivity to acetone concentration of 100 bbp (parts per billion).…”
Section: Other Applications Of Nio/с Compositesmentioning
confidence: 99%
“…Thus, due to the unique electrochemical characteristics of NiO, composite materials based on it can be used in various gas sensitive systems. For example, Fan X. et al [15] note the possibility of using a p-type composite based on NiO as a sensor for detecting gaseous acetone. Experimental results showed that the applied composite had an optimum sensor op-erating temperature in the range of 220 °C and sensitivity to acetone concentration of 100 bbp (parts per billion).…”
Section: Other Applications Of Nio/с Compositesmentioning
confidence: 99%
“…Electrospun nanofibers typically display tensile strengths below 300 MPa and Young's moduli below 3 GPa Yao et al, 2014). P(VDF-TrFE) copolymers typically have Young's moduli of approximately 1.5 GPa when made in films, while fibrous structures may have Young's modulus values as low as 6.0±2.0 MPa (Fang et al, 2010;Bhavanasi et al, 2015;Fan et al, 2015). As such, this material was expected to mimic skin's properties to some extent.…”
Section: The Effect Of Electrospinning Kraton Tm D1152 and P(vdf-trfe...mentioning
confidence: 99%